A Randomized Controlled Trial Comparing Suture-Fixation Mucopexy and Doppler-Guided Hemorrhoidal Artery Ligation in Patients with Grade III Hemorrhoids - Min Zhai; Yong-An Zhang; Zhen-Yi Wang; Jian-Hua Sun; Jie Wen; Qi Zhang; Jin-De Li; Yi-Zheng Wu; Feng Zhou; Hui-Lei Xu (Gastroenterology Research and Practice)
Background. We aimed to evaluate the effectiveness of a suture-fixation mucopexy procedure by comparing with Doppler-guided hemorrhoidal artery ligation (DGHAL) in the management of patients with grade III hemorrhoids. Methods. This was a randomized controlled trial. One hundred patients with grade III hemorrhoids were randomly assigned to receive suture-fixation mucopexy (n=50) or DGHAL (n=50). Outcome assessments were performed at 2 weeks, 12 months, and 24 months. Assessments included resolution of clinical symptoms, postoperative complications, duration of hospitalization, and total costs. Results. At 2 weeks, one (2%) patient in suture-fixation group and four (8%) patients in DGHAL group had persistent prolapsing hemorrhoids. Postoperative bleeding was observed in two patients (4%) in suture-fixation group and one patient in DGHAL group. There was no significant difference in short-term recurrence between groups. Postoperative complications and duration of hospitalization were comparable between the two groups. Rates of recurrence of prolapse or bleeding at 12 months did not differ between groups. However, recurrence of prolapse at 24 months was significantly more common in DGHAL group (19.0% versus 2.3%, p=0.030). Conclusions. Compared with DGHAL, the suture-fixation mucopexy technique had comparable short-term outcomes and favorable long-term outcomes.